WHITE OVER BLACK WHITE COAL-FINER THAN BLACK COAL - Tuhina Chatterjee. (International Journal of Innovations in Engineering Research and Technology, 2021)
White coal is a form of bio fuel produced by agriculture or forestry waste. It differs from charcoal and black coal and produces more heat than green wood. White coal is a biomass briquette which replaces fossil fuels such as lignite, coal, gas and so on. It is called white coal because it does not create any type of pollution when it’s burning.